THE USE OF SPECIAL PROPERTIES OF COLOR IN THE DESIGN-PROJECTING OF PRODUCTS - Ostapenko, N. V.; Musienko, V. O.; Rubanka, M. M.; Avramenko, A. O.; Vlasenko, V. I. (Art and Design, 2021)
The purpose of the article is to analyze the influence of the properties of the range of colors (long-wave, medium-wave, and short-wave) on a person`s feelings, his or her psycho-emotional perception, and consider these features in the design-projecting of jewelry. Also, to create further prospects for expanding the consumption of such jewelry in both domestic and foreign markets. Methodology. To conduct research, a set of general scientific approaches was used, in particular: visual-analytical, system-informational, modern methods of analysis of mechanical systems, and the method of classifications. Results. The features of the influence of color properties on the psycho-emotional perception of every person have been revealed. The designs of jewelry have been developed using some specific color ranges that will create an attractive, festive atmosphere, to identify a wider and more effective application of these features. Scientific novelty. Specific features of the influence of color and a certain color range on the formation of the appropriate psycho-emotional mood of a person have been identified, which must be considered in the design-projecting of jewelry. The variants of effective use of special properties of the color range of an enamel covering have been proposed to increase the consumers` interest in new developments of jewelry in both domestic and foreign markets. Practical significance. Practical recommendations and options for using the appropriate color range of enamel covering that can create certain psycho-emotional feelings (good mood, creative inspiration, passivity, indifference, aggression, etc.) have been proposed to extend the application of enamel coverings in the creation and development of various types of jewelry.